2015
DOI: 10.1515/epoly-2014-0200
|View full text |Cite
|
Sign up to set email alerts
|

Living radical polymerization of polyacrylamide with submicrometer size by dispersion polymerization

Abstract: Atom transfer radical dispersion polymerization of acrylamide was successfully performed in ethyl acetate/ethanol with 2,2-azobisisobutyronitrile/FeCl 2 /succinic acid as the initiating system. Polyvinylpyrrolidone was used as the stabilizer. The "living" characteristics of the polymerization were studied. A linear relationship of ln([M] 0 /[M]) vs. polymerization time was obtained. Furthermore, the molecular weight increased with monomer conversion and agreed well with the theoretical values with a narrow mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Many experiments have been carried out in different studies on the interaction of different doping materials with PVP [ 33 , 34 , 35 , 36 ] and it has been observed that the polymer composites formed reach their most homogeneous state by adding PVP. This would be due to experimental evidence showing that the use of PVP can significantly speed up the exfoliation of TMDs in composite solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Many experiments have been carried out in different studies on the interaction of different doping materials with PVP [ 33 , 34 , 35 , 36 ] and it has been observed that the polymer composites formed reach their most homogeneous state by adding PVP. This would be due to experimental evidence showing that the use of PVP can significantly speed up the exfoliation of TMDs in composite solutions.…”
Section: Resultsmentioning
confidence: 99%